204k views
2 votes
Please answer this questioncould u please answer this question

Please answer this questioncould u please answer this question-example-1

2 Answers

2 votes

es 6

Explanation:

3p-1= 5p-5-14mas4p

3p-4p-5p= -5-14mas1

3p-4p-5p= -18

3p-9p=-18

_3p=-18

p=-18:-3

p=6

User Varlotbarnacle
by
5.9k points
4 votes

Answer:

3

Explanation:

3p - 1 = 5(p-1) -2(7-2p)

(simplify)

3p -1 = 5p-5-14+4p

3p-1 = 9p-19

(make p the subject)

3p-9p = -19+1

-6p = -18

p = -18/-6

p = 3

User Chris Moore
by
5.2k points